2018
DOI: 10.4103/ijpm.ijpm_240_17
|View full text |Cite
|
Sign up to set email alerts
|

Incidentally detected asymptomatic hepatitis C virus infection with significant fibrosis: Possible impacts on management

Abstract: Serum transaminases and HCV RNA titers are poor predictors of disease severity and fibrosis. Since HCV shows a slow disease progression, higher stage may predict a worse prognosis irrespective of the low viral RNA load. Liver biopsy may help guide therapeutic decisions in IDHCV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…Although it was correlated with HAI score in the study of Zechini B et al (18), HCV-RNA was not correlated with fibrosis score. Also similarly to our study results, Gupta et al (15) revealed that HCV-RNA showed no correlation with both HAI and fibrosis. In summary, we believe that HCV-RNA should not be considered as a good indicator of liver fibrosis.…”
Section: Alt (U/l) Ast (U/l) Ast/altsupporting
confidence: 91%
See 1 more Smart Citation
“…Although it was correlated with HAI score in the study of Zechini B et al (18), HCV-RNA was not correlated with fibrosis score. Also similarly to our study results, Gupta et al (15) revealed that HCV-RNA showed no correlation with both HAI and fibrosis. In summary, we believe that HCV-RNA should not be considered as a good indicator of liver fibrosis.…”
Section: Alt (U/l) Ast (U/l) Ast/altsupporting
confidence: 91%
“…Similarly to our results, Shahid et al (13) showed that AST and ALT significantly correlated with the stages of fibrosis. However, there are some studies in literature which demonstrates that AST was better than ALT as a marker of the progression of liver damage, or that both transaminases showed no correlation with fibrosis (11,14,15,16,17,18).…”
Section: Alt (U/l) Ast (U/l) Ast/altmentioning
confidence: 99%